Endovascular management of femoral access-site and access-related vascular complications following percutaneous coronary interventions (PCI) - Schahab, Nadjib (PLoS One, 2020)
BACKGROUND: Major vascular complications (VCs) of ilio–femoral arterial access after percutaneous coronary interventions are infrequent, but are associated with increased mortality and morbidity. Routine endovascular repair of VCs is becoming the treatment of choice, especially for patients who cannot tolerate vascular surgery due to advanced cardiovascular disease or are in a bailout situation. Here, we review the different types of vascular access site complications associated with percutaneous coronary interventions (PCIs) and assess the safety and efficacy of endovascular treatment. METHODS: Data were retrospectively analysed from patients who experienced VCs after transfemoral PCIs, from December 2014 to May 2018. During this period, out of 2833 patients who underwent femoral coronary interventions, 53 (1.9%) experienced major VCs. RESULTS: In total, 40/53 (75.5%) cases with major VCs led to unplanned endovascular repair and 13/53 (24.5%) cases required surgical repair. VCs included 17 (32.1%) retroperitoneal bleeding events (BARC-2, 3a,b), 20 (37.7%) intimal dissections, and 16 (30.2%) femoral pseudoaneurysms. Overall, 32 (60.4%) patients received a covered stent, two (3.8%) received a nitinol stent, five (9.4%) patients with dissections were treated with prolonged balloon angioplasty alone, and one patient with femoral pseudoaneurysm underwent thrombin injection with simultaneous balloon occlusion. The mean hospital stay for patients after endovascular treatment was 11.06 ± 5.2 days, while for patients after surgical repair it was 17 ± 8.2 days. Endovascularly treated patients were transfused with red blood cells (13/40 32.5% vs. 2/13 15.4%) significantly more often than patients treated surgically, although surgically treated patients received more red blood cell concentrates per unit than endovascularly treated patients (1 ± 0.47 vs. 2 ± 0.93). During the one-year follow-up, no intermittent claudication was reported, and no patient required secondary endovascular or surgical repair. CONCLUSIONS: For patients who cannot tolerate vascular surgery due to advanced cardiovascular disease or are in a bailout situation, endovascular management of VCs following PCIs seems to be a feasible and safe treatment option, and represents an alternative to surgical repair in life-threatening situations. Endovascular treatment was associated with significantly fewer red blood cell concentrates per patient and fewer days in hospital than surgical treatment.